2008
DOI: 10.1590/s0102-86502008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between target-controlled-infusion and continuous-infusion anesthesia in dogs treated with methotrimeprazine and treated with propofol and remifentanil

Abstract: PURPOSE: To compare two propofol infusion techniques in bitches subjected to ovaryhisterectomy by estimating the efficiency of the propofol target-dose, evaluating the cardiorespiratory and hemogasimetric attributes, and the bispectral scale index (BIS) as well as the recovery period characteristics. METHODS: Twenty anesthetized bitches were divided into two groups of 10 each (G1, G2). Animals of G1 were pre-treated with methotrimeprazine and anesthetized with target-controlled propofol infusion by means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Efeito sinérgico tem sido relatado com o uso de alfa 2 adrenoceptores agonistas na medicação pré-anestésica, favorecendo a redução da dose de indução e de manutenção anestésica do propofol (CULLEN & REYNOLDSON, 1993;ENGLAND et al, 1996). Paralelamente, outros estudos têm demonstrado resultados satisfatórios com a infusão contínua de propofol associada a fármacos com potencial analgésico, como opióides (HATSCHBACH et al, 2008) e cetamina (MANNARINO, 2005) para obtenção de anestesia cirúrgica, com mínimos efeitos adversos (BRANSON, 2007). SELISKAR et al (2007) obtiveram valores mais elevados de freqüência cardíaca e pressão arterial média em cães anestesiados com cetamina/propofol quando comparados aos cães anestesiados somente com propofol, corroborando resultados prévios relatados por INTELIZANO et al (2008) os quais observaram maior estabilidade hemodinâmica em cães sob infusão contínua com propofol e cetamina em relação ao propofol isolado.…”
Section: Introductionunclassified
“…Efeito sinérgico tem sido relatado com o uso de alfa 2 adrenoceptores agonistas na medicação pré-anestésica, favorecendo a redução da dose de indução e de manutenção anestésica do propofol (CULLEN & REYNOLDSON, 1993;ENGLAND et al, 1996). Paralelamente, outros estudos têm demonstrado resultados satisfatórios com a infusão contínua de propofol associada a fármacos com potencial analgésico, como opióides (HATSCHBACH et al, 2008) e cetamina (MANNARINO, 2005) para obtenção de anestesia cirúrgica, com mínimos efeitos adversos (BRANSON, 2007). SELISKAR et al (2007) obtiveram valores mais elevados de freqüência cardíaca e pressão arterial média em cães anestesiados com cetamina/propofol quando comparados aos cães anestesiados somente com propofol, corroborando resultados prévios relatados por INTELIZANO et al (2008) os quais observaram maior estabilidade hemodinâmica em cães sob infusão contínua com propofol e cetamina em relação ao propofol isolado.…”
Section: Introductionunclassified
“…Four medicinal groups showed significantly lower body temperatures at the T6-T10 time points compared to the baseline. The normal body temperature range in dogs is 38.0-39.0 °C; therefore, the results evidenced a light hypothermia which was due to the central effects on thermoregulation inhibition, besides the peripheral vasodilatation brought about by propofol, which favoured the decrease in body temperature (Hatschbach et al 2008). This light hypothermia was due to practices that serve to reduce heat loss during the anaesthetic procedure such as thermal mattresses, warm fluid therapy and warm air insufflators.…”
Section: Discussionmentioning
confidence: 84%
“…Lysakowski et al (2001) studied the effects of fentanyl, alfentanil, remifentanil and sufentanil on the bispectral index during anaesthesia with propofol in humans; no significant differences were observed between the fentanyl group and the placebo group. Hatschbach et al (2008) found that the addition of remifentanil did not change the bispectral index in dogs undergoing propofol-mediated anaesthesiology. In our study, BIS values in Groups 3 and 4 were similar to the control group (Group 1) (Figure 1).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hatshbach et al [18] compared the BIS value in ovariohysterectomized dogs under propofol anesthesia or propofol anesthesia combined with remifentanyl and the BIS value was found between 73 and 79. In the present study, BIS value throughout the general anesthesia in PRO group was measured between 51 and 59.…”
Section: Tablo 1 Propofol Ve Izofluran Gruplarında Kalp Frekansı Somentioning
confidence: 99%